Structural design of an endovascular stent for treatment of an aortic aneurysm (2019)
The current models of endovascular stents havean auto-expanding biomechanism with shape memory materialwhich is able to adjust itself in the middle of implantation.These models have problems in implantation procedures in theartery; including problems of decoupling. As an alternative tothe situation, a new aortic adjustable stent was developed. Thismodel of controlled mobility aims to facilitate the implantationprocedure and the non-decoupling due to the hemodynamicactivity. A geometric design was developed, and severalsimulations were developed to analyze its biomechanicalbehavior using the Working Model program as a computationaltool. Some results were obtained that indicated the feasibilityand correct functionality of this alternative for the problem ofdecoupling and implantation.